2012
DOI: 10.1007/s10535-012-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antioxidant protection at the early stages of leaf expansion in ginkgo under natural environmental conditions

Abstract: Photosynthetic pigments, gas exchange, chlorophyll (Chl) a fluorescence kinetics, antioxidant enzymes and chloroplast ultrastructure were investigated in ginkgo (Ginkgo biloba L.) leaves from emergence to full size. Under natural conditions, the net photosynthetic rate (P N ), contents of Chl a, Chl b and total soluble proteins and fresh and dry leaf mass gradually increased during leaf expansion. The maximum photochemical efficiency of photosystem (PS) 2 (variable to maximum fluorescence ratio, F v /F m ) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Consequently, there is a growing interest in understanding Ginkgo's salinity tolerance mechanisms, especially regarding salinity stress. Current research, primarily on young Ginkgo trees, has explored aspects such as chlorophyll and chloroplast protein changes [11], osmoregulation [31], and alterations in antioxidant enzyme systems [32]. While some studies delve into Ginkgo's molecular-level salinity resistance mechanisms, there is a notable scarcity of research into the potential of exogenous hormones like melatonin in alleviating salinity stress in Ginkgo.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is a growing interest in understanding Ginkgo's salinity tolerance mechanisms, especially regarding salinity stress. Current research, primarily on young Ginkgo trees, has explored aspects such as chlorophyll and chloroplast protein changes [11], osmoregulation [31], and alterations in antioxidant enzyme systems [32]. While some studies delve into Ginkgo's molecular-level salinity resistance mechanisms, there is a notable scarcity of research into the potential of exogenous hormones like melatonin in alleviating salinity stress in Ginkgo.…”
Section: Introductionmentioning
confidence: 99%
“…SOD and CAT activities were determined using the guaiacol method. Root activity was determined using the triphenyltetrazolium chloride method [24].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Studies of Robinia pseudoacacia revealed that ROS removal by antioxidants such as APX is additionally enhanced by the presence of arbuscular mycorrhizal fungi symbiosis [74]. Increased APX activity was also observed in tobacco seedlings inoculated with arbuscular mycorrhizal fungi [196] and tomato seedlings under salt stress [197].…”
Section: Mycorrhizamentioning
confidence: 98%
“…Interestingly, in the fruit peel of tangerine x sweet orange, the level of APX decreased during the postharvest aging process and increased during drought [73]. The early stages of Ginkgo biloba L. leaf expansion were accompanied by increased activity of APX [74], emphasizing the involvement of Asc in the maximization of leaf-space to increase both the interception of light and photosynthesis. Studies on photosynthetic activity in nonwoody plants frequently focus on stress conditions such as water deficits [75] or mineral element imbalances [76].…”
Section: Agingmentioning
confidence: 99%